Primary biliary cirrhosis in early childhood – A rare case report. (August 2021) - Ullah, Kaleem; Uddin, Shams; Dogar, Abdul Wahab; Jan, Zaka Ullah; Abbas, Syed Hasnain
Abstract: Introduction and importance: Primary biliary cirrhosis (PBC) is a chronic and progressive autoimmune liver disease with no known etiology. This disease is mainly characterized by granulomatous destruction of intrahepatic biliary ducts, severe peri-portal inflammation, and ultimate progress to liver fibrosis and cirrhosis. Here, we report a five-year-old girl diagnosed with PBC, presented to us with end-stage liver disease for liver transplantation. Our patient successfully underwent liver transplantation with an uneventful recovery. This case highlights the need for awareness to report further PBC cases in the pediatric age group. Case presentation: A five-year old female child presented with a 6 months history of progressive jaundice. She had multiple admissions for hepatic encephalopathy and this time she was admitted for hepatic transplantation. On examination, she was icteric and had hepatomegaly. After thorough workup, she underwent successful hepatic transplantation and was alright post-operatively. At 6 months follow up, she is doing well. Conclusion: PBC is rare in childhood. The natural history and exact incidence of PBC in childhood are not known. Hence, there is a need for awareness to report further PBC cases in the pediatric age group. Highlights: Primary Biliary Cirrhosis (PBC) at a young age is rare. Mostly affects middle aged women (age 30 to 50). Patient usually present with progressive jaundice that can lead to end stage liver disease. In 90 percent of cases, the serologic hallmark is anti-mitochondrial antibodies (AMA). Early detection is the key to halt the progression of the disease, however, in PBC patients with end-stage liver disease, liver transplantation is the treatment modality of choice.